Gold partitioning between 1-dodecanethiol and brine at elevated temperatures: Implications of Au transport in hydrocarbons for oil-brine ore systems - Crede, L.; Evans, Katy; Rempel, Kirsten; Grice, Kliti; Sugiyama, I. (Elsevier Science BV, 2019)
Gold is can be associated with hydrocarbons in hydrothermal gold deposits, but the near-absence of experimental data on gold-hydrocarbon interactions at hydrothermal conditions prevents a quantitative interpretation of this relationship. In this study, we investigate the ability of liquid hydrocarbons to act as gold-transporting ore fluids using experiments on the partitioning of gold between brine (10 wt% NaCl) and 1-dodecanethiol (DDT). Experiments were conducted at 105 °C and 150 °C and <5 bar in a hydrothermal flow-through vessel. Partition coefficients (DAuorg/aq) obtained from the 105 °C and 150 °C experiments range from 10 ± 3.0 to 91 ± 30 at 105 °C and from 4.9 ± 0.9 to 33 ± 6.9 at 150 °C, with averages of 37 ± 33 and 21 ± 12, respectively. Gold concentrations in both the brine (<1 ppm) and DDT (up to 10 ppm) are dependent on the initial bulk concentration of gold (up to 4 ppm) and on the Au loss to the vessel walls during the experiment, as the Au concentrations correlate linearly with Au loss, while DAuorg/aq appears independent of bulk composition and Au loss. This linear dependency results in a stronger Au loss from the oil that bears more Au (DDT), and enables the calculation of DAuorg/aq for zero Au loss, which is 19 ± 21. These findings indicate that DAuorg/aq is a constant at the P-T-X conditions investigated. While these experiments did not directly assess Au solubility in DDT, no indication of Au saturation was observed, suggesting that higher concentrations are possible. The pH of the brine decreases during the experiments, indicating that the DDT underwent deprotonation and possibly decomposition during the partitioning reaction, but the pH does not have an observable effect on the gold concentrations in the brine and DDT. Preferential partitioning of gold into DDT is attributed to bonding with the thiol group, and as thiols compose up to 7 wt% of the total organic sulfur content of crude oils, liquid hydrocarbons have the potential to transport significant amounts of gold in ore formation processes. This is of importance for ore systems forming at relatively low temperatures and ore deposits known to be associated with organic matter such as Carlin type Au deposits.